2015
DOI: 10.1590/0102-33062014abb3420
|View full text |Cite
|
Sign up to set email alerts
|

Response of an endangered tree species from Caatinga to mycorrhization and phosphorus fertilization

Abstract: Schinopsis brasiliensis is an endangered tree species found in the Caatinga biome. It presents a characteristic slow development and difficult propagation, although it has been traditionally exploited in the region. Application of arbuscular mycorrhizal fungi (AMF) and phosphorus (P) fertilization may be beneficial to S. brasiliensis development at the seedling stage, which at the same time may help species conservation and the recovery of degraded areas in the Caatinga biome. We assessed the response of S. br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
2
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
(28 reference statements)
1
5
2
1
Order By: Relevance
“…With regard to Fe concentration, the decrease in its uptake in plants inoculated with increasing doses of P agrees with the latest data of Oliveira et al (2015), who evaluated the response of Schinopsis brasiliensis Engl. to inoculation with AMF and P fertilization.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…With regard to Fe concentration, the decrease in its uptake in plants inoculated with increasing doses of P agrees with the latest data of Oliveira et al (2015), who evaluated the response of Schinopsis brasiliensis Engl. to inoculation with AMF and P fertilization.…”
Section: Discussionsupporting
confidence: 89%
“…The decrease in growth response at increasing doses of SSP confirms the benefits of mycorrhizal inoculation in soils with low P values. C. etunicatum provides higher growth rates, even in very fertile soils, unlike what Oliveira et al (2015) found, in which C.…”
Section: Discussioncontrasting
confidence: 78%
“…This result is in line with those of Mbogne et al (2015) on pumpkins and Temegne et al (2017b) on Bambara groundnuts. De Oliveira et al (2015) also showed that AMF increases plant development at low P levels.…”
Section: Discussionmentioning
confidence: 94%
“…Mbogne et al (2015) and Temegne et al (2017) found that chemical fertilizer did not affect the frequency of mycorhization. In addition, Oliveira et al (2015), showed that mycorrhization increases the plants development at low P levels. Ingleby et al (2001Ingleby et al ( , 2007 have shown that high supply of soluble P i decrease mycorrhizal infection rate and may eliminate the positive effects of this association on plant yield.…”
Section: Results and Discussion Effect Of Mycorrhization And P Imentioning
confidence: 99%